Evaluation of temporal variability on tissue nutrient concentrations of canola. Issue 1 (10th January 2022) - Reed, Vaughn; Sutradhar, Apurba K.; Arnall, D. Brian; Lofton, Josh
Abstract: The use of plant tissue analysis as a tool for diagnosing nutrient deficiency has steadily gained interest by producers and crop advisors in Oklahoma. A study was conducted during the 2012–2013 and 2015–2016 growing seasons at two locations near Stillwater and Perry, OK, to evaluate the variability of canola ( Brassica napus L.) nutrient concentrations across various growth stages (STAGE), among several days within each growth stage (DAY), across several times during the day (TIME). Canola tissue samples were collected in the morning, noon, and evening for three consecutive days at rosette, postdormancy break, and prebolting stages. Samples were analyzed for macronutrients (N, P, K) and secondary (S, Ca, Mg) nutrient concentrations. Tissue nutrient concentrations were found to be extremely variable, as affected by main effects and interactions of sampling TIME, DAY, and STAGE. Nutrient concentration generally increased over time, for most nutrients. The analysis did not indicate any definitive pattern of tissue nutrient accumulation based on the fixed effects TIME and DAY. Although, the exact reasons for the different responses are not known, they may be related to soil physical and chemical property differences and variation in weather factors. While this work does not provide insight in the relationship between nutrient concentrations and crop yield, this does bring to light complications with using tissue analysis for management decisions. Further work must be done to investigate the relationships of tissue concentration and yield, and the viability of tissue sampling for nutrient management. Core Ideas: Canola tissue nutrient concentrations were affected by TIME, DAY, and STAGE samplings. Stage of sampling produced the greatest changes in concentration. The effects of TIME, DAY, and STAGE samplings were inconsistent across nutrients.